Faktor-Faktor yang Berhubungan dengan Kejadian Filariasis di Kabupaten Barito Kuala - Rahmat, Agus; Rahmayanti, Devi; Rachmawati, Kurnia (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Filariasis (elephantiasis disease) is an infectious disease caused by filarial worm (microfilaria) andtransmitted by mosquitoes Mansonia, Anopheles, Culex, Armigeres and Aedes. In 2012 Barito KualaRegency was declared endemic filariasis with Mf-rate of 2.19%. The purpose of this study was to studycommunity and environmental factors related to the incidence of filariasis in Barito Kuala Regency. Thisstudy used a case control design. The sampling technique used purposive sampling with a number ofsamples with a sample of 15 people and controls 30 people with a ratio of 1: 2. The research instrumentwas in the form of a questionnaire sheet and observation sheet. Data analysis using chi-square test. Theresults of this study indicates that there was a relationship between the habit of using bed nets and theincidence of filariasis with a value of p = 0.015 OR: 6.91, there was a relationship between the habit ofusing wire netting in interactions with the incidence of filariasis with a p value of 0.441 OR: 2.04 with theincidence of filariasis with a value of p = 0.011 OR: 14.00, there was no association between the habit ofusing mosquito repellent and the incidence of filariasis with p = 0.044 OR: 5.23, and there was noassociation with water hyacinth with the incidence of filariasis with p = 0.587 OR: 1.75. The habit of usingmosquito nets, wire netting during operations, and managing marine use filariasis.